Filipinorhynchus Cabras gen. nov., with two new species (Coleoptera, Curculionidae, Entiminae, Pachyrhynchini) from Davao de Oro, Mindanao Island, Philippines - Cabras, Analyn A.; Agbas, Daven Jayson D.; Obrial, Graden G. (Zootaxa, 2025)
Filipinorhynchus Cabras gen. nov. with F. engkanto Cabras, Obrial and Agbas sp. nov. and F. diwata Cabras, Obrial and Agbas sp. nov. are described from Davao de Oro, Mindanao Island, Philippines. The new genus is distinguished from all other Pachyrhynchini by its relatively large size; dull, matte body surface; prothorax and elytra punctate with rough surface, devoid of scales mostly covered with setae; and elytra narrowly elongate, fully covered with homogenously arranged and moderately long erect setae along striae. The new genus is closely related to the genus Pachyrhynchus Germar, 1824 particularly the P. orientalis and P. speciosus species groups; however, it clearly differs from the latter by the presence of a transverse groove separating the head and rostrum.